Gender Transformative Methodologies CoP. Step-by-step guide: Integrating GTAs in the project cycle - Safa Barraza, Alejandra; Bailey, Arwen (2025)
During this session, participants heard about the Step-by-Step Guide, developed within the framework of the JP GTA, which provides step-by-step detailed guidance for project and programme staff on how to integrate the gender transformative approach at every phase of the project cycle. It also provides examples of practical tools and methodologies that can help build agency for women and men and transform unequal power relations and discriminatory social institutions. This guide emphasizes the need for structural changes to create more equitable systems through the design and implementation of projects and programmes.